THE INFLUENCE OF STRATEGIC MANAGEMENT ACCOUNTING ASPECTS ON BANK PERFORMANCE - Idzna Nur Shodriani; Khairina Nur Izzaty (State Islamic Institute (IAIN) Tulungagung, 2022)
This research purpose to develop a broad conceptualization of strategic management accounting and examine the influence of aspects of strategic management accounting on organizational performance at commercial banks and BPR in Tegal. This type of research is quantitative and the data analysis uses SPSS ( Statistical Product and Service Solutions ) 25. The sampel of this research is the head of the office leadership of commercial bank and BPR in Tegal. The result of this research indicate that organizational structure and organizational climate hanve a positive effect on organizational performance while organizational resources and information system have no effect on organizational performance.